Risk and Temporal Changes of Heart Failure Among 5‐Year Childhood Cancer Survivors: a DCOG‐LATER Study - Elizabeth A. M. Feijen; Anna Font‐Gonzalez; Helena J. H. van der Pal; Wouter E.M. Kok; Ronald B. Geskus; Cécile M. Ronckers; Dorine Bresters; Elvira C van Dalen; Eline van Dulmen‐den Broeder; M. van den Berg; Margriet van der Heiden‐van der Loo; Marry M. van den Heuvel‐Eibrink; et al. (2018)
Background Heart failure is one of the most important late effects after treatment for cancer in childhood. The goals of this study were to evaluate the risk of heart failure, temporal changes by treatment periods, and the risk factors for heart failure in childhood cancer survivors ( CCS ). Methods and Results The DCOG‐LATER (Dutch Childhood Oncology Group–Long‐Term Effects After Childhood Cancer) cohort includes 6,165 5‐year CCS diagnosed between 1963 and 2002. Details on prior cancer diagnosis and treatment were collected for this nationwide cohort. Cause‐specific cumulative incidences and risk factors of heart failure were obtained. Cardiac follow‐up was complete for 5,845 CCS (94.8%). After a median follow‐up of 19.8 years and at a median attained age of 27.3 years, 116 survivors developed symptomatic heart failure. The cumulative incidence of developing heart failure 40 years after childhood cancer diagnosis was 4.4% (3.4%–5.5%) among all CCS. The cumulative incidence of heart failure grade ≥3 among survivors treated in the more recent treatment periods was higher compared with survivors treated earlier (Gray test, P =0.05). Mortality due to heart failure decreased in the more recent treatment periods (Gray test, P =0.02). In multivariable analysis, survivors treated with a higher dose of mitoxantrone or cyclophosphamide had a higher risk of heart failure than survivors who were exposed to lower doses. Conclusions CCS treated with mitoxantrone, cyclophosphamide, anthracyclines, or radiotherapy involving the heart are at a high risk for severe, life‐threatening or fatal heart failure at a young age. Although mortality decreased, the incidence of severe or life‐threatening heart failure increased with more recent treatment periods.